4-ethylamino-3-nitrobenzoic acid - Narendra Babu, Shivanagere Nagojappa; Abdul Rahim, Aisyah Saad; Abd Hamid, Shafida; Quah, Ching Kheng; Fun, Hoong-Kun (International Union of Crystallography, 2009)
In the title compound, C9H10N2O4, an intramolecular N-H...O hydrogen-bond interaction generates an S(6) ring motif. The nitro group is slightly twisted away from its attached benzene ring [dihedral angle = 15.29 (15)°]. In the crystal structure, molecules are stacked down the a axis caused by short O...O(-1-x, -y, 2-z) contacts of 2.6481 (16) Å involving the O atoms of the nitro groups. The crystal packing is consolidated by intermolecular O-H...O hydrogen bonds, linking the molecules into centrosymmetric dimers.